2013
DOI: 10.1007/s00421-013-2605-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training combined with vascular occlusion or hypoxia on neuromuscular function in athletes

Abstract: The aim was to investigate the effects of low-load resistant training combined with vascular occlusion or normobaric hypoxic exposure, on neuromuscular function. In a randomised controlled trial, well-trained athletes took part in a 5-week training of knee flexor/extensor muscles in which low-load resistant exercise (20% of one repetition maximum, 1-RM) was combined with either (1) an occlusion pressure of approximately 230 mmHg (KT, n = 10), (2) hypoxic air to generate an arterial blood oxygen saturation of ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 37 publications
3
82
0
6
Order By: Relevance
“…Likewise, Manimmanakorn et al [29] observed substantially greater increases in strength (3 s MVC) and muscular endurance (30 s MVC and number of repetitions to failure at 20% 1RM), following 5 weeks of training in the IHRT group than a normoxic control group. Similar results were presented in a subsequent study [121], with a small effect (0.44) for IHRT versus the control condition for 3 s MVC, and moderate effects (0.64 and 0.70) for 30 s MVC and number of repetitions to failure at 20% 1RM between these conditions, respectively. While these data suggest that IHRT can accelerate increases in muscle strength, Friedmann et al [120] observed no significant changes in maximum strength or muscular endurance following such a program.…”
Section: Increases In Muscular Strengthsupporting
confidence: 85%
See 2 more Smart Citations
“…Likewise, Manimmanakorn et al [29] observed substantially greater increases in strength (3 s MVC) and muscular endurance (30 s MVC and number of repetitions to failure at 20% 1RM), following 5 weeks of training in the IHRT group than a normoxic control group. Similar results were presented in a subsequent study [121], with a small effect (0.44) for IHRT versus the control condition for 3 s MVC, and moderate effects (0.64 and 0.70) for 30 s MVC and number of repetitions to failure at 20% 1RM between these conditions, respectively. While these data suggest that IHRT can accelerate increases in muscle strength, Friedmann et al [120] observed no significant changes in maximum strength or muscular endurance following such a program.…”
Section: Increases In Muscular Strengthsupporting
confidence: 85%
“…control). While all groups demonstrated significantly greater muscle activation during strength and endurance tasks following training, the largest increases were reported in the BFR group [121]. This may suggest that the neuromuscular changes were most influenced by the restriction of blood flow, rather than hypoxia per se.…”
Section: Skeletal Muscle Functionmentioning
confidence: 84%
See 1 more Smart Citation
“…While the vast majority of BFR research has been conducted using untrained participants, several investigations have also demonstrated muscular benefits from BFR in athletic populations [5,[11][12][13][14][15][16][17]. As these individuals have already achieved a high level of muscular development, low-load resistance training would not normally facilitate such benefits, suggesting that the addition of BFR stimulates these responses.…”
Section: Adaptive Responses and Potential Mechanisms Underpinning Bfrmentioning
confidence: 99%
“…Numerous investigations have reported beneficial muscular adaptations to BFR training in athletes [5,11,13,14,16]. Furthermore, these adaptive responses have translated into enhanced performance across a range of athletic tasks, including maximum strength [5,14,16], countermovement jump power [5], maximal and repeated sprint performance [5,13,14], agility performance [14] and an aerobic shuttle run test [14].…”
Section: Healthy and Athletic Participantsmentioning
confidence: 99%